Problems in teaching english academic writing among ESL lecturers at public and private universities in Malaysia - Azmar, Khairunnisa; Razali, Abu Bakar (Scientia Socialis, 2024)
English academic writing is fundamental at tertiary level as it is the main medium of communication in the academe. Over the years, ESL lecturers have not only struggled to search for the most suitable teaching approach(es) to teach academic writing but have encountered several other problems in their teaching, such as class size, students’ English proficiency levels, heavy workload, and others. Given these circumstances, a review of the literature has indicated there are scant studies that explore the problems faced by ESL lecturers where comparisons are made between public and private universities. Grounded in multiple case studies, four ESL lecturers from two public and two private Malaysian universities were purposively selected for the study. Data were collected from semi-structured in-depth interviews, lesson observations, and document analysis. A total of 12 interview transcripts were transcribed verbatim by the researchers, and data were analysed thematically using thematic analysis and cross-case analysis, where emerging themes were used to present the findings. Findings reveal that ESL lecturers at higher education institutions encountered problems, such as constraints in time, marking issues, students’ lack of interests and motivations, lecturers’ lack of interest in writing, lecturers’ lack of content and pedagogical content knowledge, and lack of institutional support. Hence, professional support should be given to ESL lecturers to overcome their teaching problems, and future research should explore the strategies employed by ESL lecturers to alleviate their teaching problems.